Rehabilitacija ljudi po amputaciji - Burger, Helena (Rehabilitacija (Ljubljana), 2010)
The article presents the level of the evidence that exists in the literature on rehabilitation of people after lower and upper limb amputation. We found that there is not much high-quality evidence available in this field of rehabilitation.
Keywords: amputacija; hand; noge; proteze; rehabilitacija; roke; vocational rehabilitation